(untitled) (Al-Academy, 2024)
The research problem lay in the existing of this direct relation between the increasing and the big variety of the goods and the producing companies which mean the increase of the competition and the directing techniques of the commercial advertisings, which become spread everywhere and in an age characterized with the great varieties in the tests and the stances which requires the designers to seek designing accomplishments that are characterized with creativeness , seriousness and unsallity through the designer depending in constructing his / her texts and his/ her visual items on reference forms metaphors to achieve his / her designing purposes. So the researcher through her primary flying study seek the identifying the manner of the form followed in the designing of printed commercial advertisements , and she evoke in the light of what came above, the following questions which some of which are: 1. Is there a suitability between that which is metaphor taking for and the goods? 2. Did the metaphor acquire aesthetic reference added to the designed work and the centers of attraction ? The study included fiove chapters, chapter one tackled the research problem, its importance, its goals, its limits and identifying its idioms, as for chapter two, it contain the theoretical frame and its divided into three inquiries the firsat tackled the concept of metaphor –sources types and its reference function, as for the second inquiry it tackled the concept of reference in designing and form reference in designing of commercial advertisements , while inquiry three tackled the sign reference in the commercial advertisement, and then followed in the indicators which come from the theoretical frame. Then the researcher tackled the research procedures in chapter three and in chapter four the samples were analyzed and discussed basing to the theoretical frame indicators, while chapter five came to include the results and the inferences reached by the researcher. The most important results : the designer ability in building the advertisement subject, its embodying, his / her awareing with the directing techniques frames "the technique of showing the idea" and his / her seeking the reference form metaphors, represent main variable in the building of modern advertisement in designing and in directing. The designer depended in her designing on the receiver awairing and his / her awairing to the reference mark mentally –illusion in a way that the written texts may vanish except the titles.